The application of article 1320 CC as public policy in Spanish law. Regarding the resolution of 31 January 2022, of the Directorate General For Legal Certainty and Public Faith - Rodríguez Rodrigo , Juliana (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The RDGSJyFP of 31 January 2022 analyses whether the sale of a property, carried out by the three co-owners of the property, requires the consent of the spouse of one of them because it is the couple’s habitual residence. The requirement of the consent of the spouse who is not the owner of the habitual residence may be imposed by the law governing the matrimonial property regime or it may have to be applied as part of the public policy of the forum. In our case, the law governing the property relations of the spouses is the British law, by virtue of the first connection of Article 9(2) CC, and, according to it, there is complete freedom for the spouse to dispose of his or her personal property. For this reason, the question arises as to whether the consent of the non-owner spouse can be required by application of Article 1320 CC, as a public policy rule of Spanish law. Finally, it is considered that the property does not constitute the habitual residence of the couple and, therefore, the consent of the spouse is not necessary for the sale of the property to be valid and registrable.